Impact of Education Level on Waist Circumference Among University Workers - Tira Alfiani Laariya; Cita Eri Ayuningtyas; Nurul Putrie Utami; Fauzan Achmad Maliki (JURNAL IMPLEMENTA HUSADA, 2025)
Introduction: Waist Circumference (WC) may be a more accurate indicator of obesity than BMI because it is a simple and more practical method of assessing abdominal fat deposition. The level of education may be associated with waist circumference. The study aims to investigate the relationship between educational level and waist circumference (WC) among workers at a university in Yogyakarta. Method: The study enrolled 497 participants as part of a medical check-up event in December 2022, using a total sampling approach. Education level was determined by secondary data and classified into two groups: group I (senior high school and bachelor's degrees), and group II (master's and postgraduate degrees). Mann-Whitney and logistic regression models were used to estimate associations. Result: There were significant mean differences in WC between group I (82.83 cm) and group II (93.13 cm) with a p-value 0.05. WC was significantly higher among university workers with higher education levels.  A higher degree of education had 2,4 greater risks for higher WC than others (OR: 2,464 [1,674-3,627]). Discussion: Higher WC is strongly associated with a higher level of education in this study. University workers with higher levels of education should be the primary target of public health programs aimed at reducing obesity.